Improved environmental multimedia modeling and its sensitivity analysis - Yuan, Jing (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
Modeling of multimedia environmental issues is extremely complex due to the intricacy of the systems with the consideration of many factors. In this study, an improved environmental multimedia modeling is developed and a number of testing problems related to it are examined and compared with each other with standard numerical and analytical methodologies. The results indicate the flux output of new model is lesser in the unsaturated zone and groundwater zone compared with the traditional environmental multimedia model. Furthermore, about 90% of the total benzene flux was distributed to the air zone from the landfill sources and only 10% of the total flux emitted into the unsaturated, groundwater zones in non-uniform conditions. This paper also includes functions of model sensitivity analysis to optimize model parameters such as Peclet number (Pe). The analyses results show that the Pe can be considered as deterministic input variables for transport output. The oscillatory behavior is eliminated with the Pe decreased. In addition, the numerical methods are more accurate than analytical methods with the Pe increased. In conclusion, the improved environmental multimedia model system and its sensitivity analysis can be used to address the complex fate and transport of the pollutants in multimedia environments and then help to manage the environmental impacts